Pembaruan Hukum Islam dalam Perspektif Ijtihad Imam al-Syafi'i: Analisis Transformasi Qaul Qadim dan Qaul Jadid terhadap Dinamika Perubahan Sosial - Armaya Azmi (Yayasan Dar Arrisyah Indonesia, 2024)
The dynamic development of society has generated various emerging legal issues that require continuous renewal within Islamic legal thought. In this context, Imam al-Shafi'i's ijtihad through the transformation from qaul qadim to qaul jadid represents a significant model of Islamic legal reform, demonstrating that fiqh is not a static body of law but is capable of reformulation in response to social, cultural, political, and intellectual changes while maintaining the authority of the Qur'an and Sunnah as the primary sources of Islamic law. Although studies on qaul qadim and qaul jadid have been widely conducted, most remain descriptive and historical, with limited attention given to their epistemological significance and their relevance to contemporary Islamic legal reform, particularly within the Indonesian legal context. This study aims to analyze the transformation of Imam al-Shafi'i's legal reasoning, identify the factors underlying his revision of legal opinions, and examine its implications for contemporary Islamic legal development. This normative legal research employs conceptual, historical, and usul al-fiqh approaches. Data were collected through library research using Imam al-Shafi'i's primary works, classical Islamic legal literature, and recent national and international scholarly publications, which were analyzed using qualitative descriptive methods. The findings reveal that the transition from qaul qadim to qaul jadid should not be understood as inconsistency but rather as evidence of methodological flexibility in Islamic legal reasoning that accommodates stronger textual evidence, changing social realities, local customs, and public interest (maslahah) within the framework of Islamic legal methodology. This study argues that Islamic legal reform should integrate textual authority, methodological rigor, and contextual awareness. It contributes theoretically by reaffirming that legal renewal is an inherent epistemological process within the Islamic legal tradition and offers practical implications for the development of Indonesian Islamic law in addressing contemporary societal changes while preserving its normative legitimacy.